The embodied and the cultural in the conceptualization of pitch space in Croatian - Kiš Žuvela, Sanja (Array, 2019)
Most conceptual metaphors that conceptualize musical pitch rely heavily on human perception, images and experience structured through spatial and orientation image schemas such as the schema of verticality. The paper analyses conceptual metaphors that structure pitch relations in terms of vertical space, thickness and size as they appear in the Croatian musical terminology. The image schemas of verticality and size are analysed within the conceptual metaphors pitch relations are relations in vertical space and pitch relations are relations in size in order to define to what extent their motivation is embodied and universal, and what can be attributed to cross-cultural and cross-linguistic influences present in the creation and understanding of music terminology in Croatia.